BS ISO 13044-2. Road vehicles. Fully automatic coupling systems 24 V (FACS) for heavy commercial vehicle combinations. Part 2. Electrical and pneumatic interface for 50 mm fifth wheel couplings (27th November 2019) - British Standards Institution,
No abstract available